Perancangan Sistem Informasi Inventory Barang Berbasis Web Menggunakan Metode Waterfall - Riska Yanti; Wawan Kurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study addresses inventory management issues at PT. BPI Jakarta, where manual recording processes have led to data inconsistencies, slow information retrieval, and limited stock monitoring. The purpose of this research is to design and develop a web-based inventory information system that improves data accuracy and accelerates administrative processes. The Waterfall method is applied as a structured system development approach, consisting of requirements analysis, system design, implementation, and testing stages. Data collection was conducted through direct observation and interviews with relevant stakeholders. The system was developed using the CodeIgniter 4 framework with PHP as the programming language and MySQL as the database management system. The resulting system provides features for managing inventory data, recording incoming and outgoing goods, handling item borrowing, and automatically presenting stock information. Black-box testing results indicate that all system functionalities operate as expected, demonstrating that the system enhances operational efficiency and improves the accuracy of inventory management.